ORGANIZATIONAL AGILITY IN THE TELECOMMUNICATIONS SECTOR: LEADERSHIP AND CHANGE CAPABILITY IN ZIMBABWE - Robert , Tawanda Moyo; Ndlovu, Grace Chipo (Current Journal of Human Resource Management (CJHM), 2024)
This study investigates the impact of leadership and change capability on organizational agility within Zimbabwe’s major mobile network providers. Organizational agility, a contemporary focus in organizational research, is shaped by factors such as leadership and change capability. Historically, organizations maintained competitive advantages through low competition and high entry barriers. However, globalization has lowered these barriers, enabling new competitors to challenge established entities, thus heightening the need for agility. With rapid technological advancements, organizations must adapt to stay competitive. This research examines three leading mobile network providers in Zimbabwe: Econet Wireless, Net One Zimbabwe, and Telecel Zimbabwe, focusing on the role of leadership and organizational change capability. Utilizing a mixed-methods approach, the findings demonstrate that emphasizing change capability and shared leadership fosters organizational agility. Statistical analysis confirms a strong correlation between leadership, change capability, and agility, with hypothesis testing yielding a 95% significance interval. The proposed model offers valuable insights for organizations seeking to enhance their agility in a competitive market.